CD56briCD38+ as a novel neutrophil-specific marker in chronic myeloid leukemia - Panpan Huang; Cuiping Zhang; Aimei Zhang; Ju Mao; Gan Liu; Chaojie Hu; Huaiping Zhu (Heliyon, 2024)
Background: Chronic myeloid leukemia (CML) is classified as a subtype of myeloproliferative neoplasm, and bone marrow flow cytometry does not reveal any specific immunophenotype. Interestingly, aberrant expression of cluster of differentiation (CD) markers such as CD56 and CD38 has been observed on neutrophils in CML patients. Therefore, we investigated the abnormal expression of CD56 and CD38 in CML neutrophils to explore their diagnostic value in identifying CML through flow cytometry. Methods: We have developed a multi-parameter flow cytometry assay to identify aberrant immunophenotypes in CML neutrophils among bone marrow nucleated cells. Results: Compared to healthy donors and patients with a reactive neutrophilia or other hematological malignancies, the percentage of CD56briCD38+ neutrophil subsets in CML patients exhibits a distinctive increase (cut-off value, 2.0 %). The specificity and sensitivity associated with the learning cohort (168 samples) were 90.8 % and 84.9 %, respectively, while in the validation cohort (194 samples), they were 90.7 % and 84.7 %. The accumulation of CD56briCD38+ neutrophil subsets, which demonstrate are abnormal characteristics, is independent of the neutrophil count, BCR/ABL1 fusions and risk stratification but associated with blast cells immunophenotype. Moreover, this increase disappears in CML patients after treatment with tyrosine kinase inhibitors when the curative effect was satisfactory. Conclusions: We conclude that an increase in the proportion of CD56briCD38+ neutrophil subsets exceeding 2.0 % of total neutrophils serves as a highly sensitive and specific flow cytometry marker, enabling rapid and accurate identification of CML.